1986
DOI: 10.1159/000206032
|View full text |Cite
|
Sign up to set email alerts
|

HLA Antigens, Blood Groups and Immunoglobulin Levels in Idiopathic Thrombocytopenic Purpura

Abstract: Thirty-three patients with idiopathic thrombocytopenic purpura (ITP) were tested for HLA-A, B and C antigens, platelet antibodies, immunoglobulin levels and ABO blood groups. With one exception, ITP proved not to be significantly associated with the HLA antigens studied; an increased frequency of HLA-A28 was found in chronic ITP patients (50 vs. 18.7% in the control population). An increased incidence of blood group A was found in ITP patients (64 vs. 37.98% in the control population), especially in those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Indeed, single associations of HLA-B8, -B12 [8], and -A28 [9] with ITP have been described; moreover, HLA-A3/B7/DR2 and HLA-A26/ B38/DR2 haplotypes, which are discrepant in their class I components, were also found to be associated with ITP [10]. On the other hand, further studies have not confirmed any class I association with ITP [30 -33], and different MHC class II alleles, HLADRB1*0410 and HLADRB1*0101, were associated with the disease in distinct studies [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, single associations of HLA-B8, -B12 [8], and -A28 [9] with ITP have been described; moreover, HLA-A3/B7/DR2 and HLA-A26/ B38/DR2 haplotypes, which are discrepant in their class I components, were also found to be associated with ITP [10]. On the other hand, further studies have not confirmed any class I association with ITP [30 -33], and different MHC class II alleles, HLADRB1*0410 and HLADRB1*0101, were associated with the disease in distinct studies [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors can influence the development of autoimmune diseases, especially immune-response genes, including the human leukocyte antigen (HLA) genes. Indeed, some association studies have indicated genetic polymorphisms on HLA genes as predisposing factors to ITP [5][6][7][8][9][10]. However, the associations reported were generally weak and varied among the studies.…”
Section: Introductionmentioning
confidence: 99%
“… a synonymous: BLYS, CD257, TALL-1, TALL1, THANK, TNFSF20 b aITP= acute ITP, cITP= chronic ITP c not reported in more detail d other HLA typing studies (3336) have discrepant results and used the non-genetic two-stage microlymphocytotoxicity test according to the NIH Tissue Typing Manual. Therefore these reports are not reported in this table.…”
Section: Tablesmentioning
confidence: 99%
“…HLA alleles found to be associated with ITP include HLA-B8 and -B12 in adult patients with chronic ITP [11], Aw32 in children with acute ITP [12], and HLA-A28 in chronic ITP patients [13]. The presence of HLA-DRw2 was also significantly increased in ITP patients along with the co-occurrence of either A3 and B7 (known to be in linkage disequilibrium with DRw2) or A26 and Bw38 [14].…”
Section: Introductionmentioning
confidence: 96%
“…HLA studies that associated ITP with a particular HLA allele can potentially be explained by sampling error from heterogeneity of the population, regional differences in HLA frequency, different diagnostic criteria for ITP that accounts for the HLA association, or linkage disequilibrium [13,15,22]. In addition, most of the studies were done 20 -30 years ago when HLA antisera and HLA alleles were not as well defined.…”
Section: Introductionmentioning
confidence: 99%